Alternatives for airport management in Brazil: The case of the innovative management model of the Zona da Mata regional airport - Vitor Augusto Martins da Costa; Danielle Carvalho Ribeiro (Innovation & Management Review, 2019)
Purpose - This paper aims to answer the following question: Is PPP a financially viable alternative for the management of regional airports in Brazil? Design/methodology/approach The methodology is based on the case study of the innovative model of Zona da Mata Regional Airport management. It was used Value for Money as a method to compare this case with the conventional airport management alternative. Findings It was observed that, when compared to the airport management alternative through contracting third parties, the public-private partnership (PPP) provided a reduction of almost 70% of public spending on the management of this infrastructure. Besides the financial advantage, other benefits of this PPP contract were also observed. Research limitations/implications The analyses carried out in this study are not exhaustive and can be improved and remade as the life cycle of the PPP contract studied is progressed. Practical implications It was concluded, from the results found, that PPP is an efficient alternative for the management of regional airports in Brazil, and the model can be replicated for similar airports. Originality/value When analyzing the results of this innovative project of managing a regional airport through a PPP, this work made it possible to measure the positive impacts of this alternative and demonstrate the potential of the PPP as an alternative for the management of other regional airports in Brazil
Keywords: 650; Process innovation; Public-private partnerships; Regional airports